Comparative Analysis of a Rectifier Performance in Power Generation Applications - Sri Agustina; Herlina Wahab; Djulil Amri; Al Denton Mourzade (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
Electrical energy's significance is critical to human life, as seen by the rising usage of this resource. Electricity-consuming machinery and technology are developing at an accelerating rate. A substantial electrical power supply is required to achieve these requirements. An effective method to address this issue is to use a generator set powered by an electric motor. This generator necessitates the use of a converter, which serves the purpose of transforming alternating waves (AC) into direct waves (DC), generally referred to as a rectifier. The rectifier's unsatisfactory performance necessitates the need for this research, which seeks to develop and construct a rectifier and subsequently compare its performance utilizing two distinct current sources. Rectifier performance is obtained through the utilization of direct computation and measuring methods. Two sources charge the battery: direct current from the motor and alternating current from the power grid. According to the test results, the converter using an electric power plant source had a higher current value. On the generator, the battery charges up to 13.4 volts in 55 minutes, which is 5 minutes quicker than on the PLN source.